Les pratiques préventives auprès des travailleurs d’agences de location de personnel temporaire ou permanent : comparaison entre les travailleurs immigrants et non immigrants - Jessica Dubé; Sylvie Gravel (Perspectives Interdisciplinaires sur le Travail et la Santé)
Studies show that the frequency of occupational injuries among workers from personnel placement agencies is higher than that of other workers in the industrial sectors in Québec. The lack of regulations concerning the triangular work relations between the client company, the agency, and the worker would seem to be the main factor explaining the negligent protection of their occupational health and safety (0HS). The present article describes preventive OHS practices that were provided for 42 workers from placement agencies in the Québec City and Montréal regions. The qualitative analysis compared immigrant and non-immigrant workers’ exposure to risks, their access to training and personal protection equipment, and the support they received for declaring an occupational injury whenever they had an accident or became ill. The results demonstrated that immigrant workers who turn to placement agencies to enter the work market were assigned the most difficult and dangerous jobs. Neither the agencies nor the client companies insured adequate protection, and the permanent company workers often ignored them.